A Comprehensive in silico Analysis of mt-CO1 gene of Fasciola hepatica - Celik, F.; Simsek, S.; Kesik, H. K.; Kilinc, S. G. (Hellenic Veterinary Medical Soc, 2022)
This study was conducted for the aim of comprehensive evaluation of the genetic diversity and phyloge-netic relations of F. hepatica among various hosts. In the current work, published mt-CO1 gene sequences belonging to final hosts of F. hepatica were used to create the dataset. First of all, 478 sequences were obtained with PubMed search. Then, some shorter sequences were removed after alignment, and 319 sequences which included cattle (n=242), sheep (n=46), goat (n=5), donkey (n=8), bison (n=7), buffalo (n=7), human (n=2) and camel (n=2) sequences were examined in the MEGA X. The existence of 72 haplotype groups was detected. The most polymorphic sites (n=42) containing 31% (13/42) parsimony informative sites were detected in Iranian isolates. The mt-CO1 network involved of 35 hap-lotypes, 80% out of which were geographically unique. However, a main haplotype consisting of 39.2% of the total isolates was formed. The bison isolates of F. hepatica showed the maximum haplotype variety within the final host isolates, followed by the sheep, buffalo, cattle, goat and donkey isolates. The genetic varity of F. hepatica in different hosts and countries revealed the possibility of new strains appearing in the future.
Keywords: Fasciola hepatica; in silico analysis; mt-CO1; haplotype